Analysis of Character Education Values in Minhājul Muta‘allim by Imam Al-Ghazali - Muhammad Fadhil Hadziq; Muhammad Aqil Abror (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study explores the values of character education contained in Minhājul Muta‘allim by Imam Al-Ghazali, emphasizing their relevance to modern education. The research arises from growing concerns about moral decline among students in the 21st century, where education often prioritizes intellectual growth over ethical and spiritual formation. The study aims to identify and analyze Al-Ghazali’s moral framework in relation to the 18 national character education values promoted by Indonesia’s Ministry of Education and Culture. Employing a descriptive qualitative approach with content analysis, the research examines both the primary text and supporting literature to extract and categorize character values such as religiosity, honesty, discipline, responsibility, and social care. Findings reveal that Minhājul Muta‘allim integrates intellectual, moral, and spiritual dimensions of learning, emphasizing sincerity, respect for teachers, independence, and the social application of knowledge. These values align closely with Indonesia’s national education character framework and demonstrate that classical Islamic pedagogy offers timeless principles for holistic education. The study concludes that Al-Ghazali’s ethical model remains highly applicable to contemporary education and contributes theoretically by linking classical Islamic ethics with modern character education, and practically by offering a culturally grounded model for moral and educational development.